Analisis Pengaruh Halal Awareness, Religiusitas, Gaya Hidup, dan Viral Marketing terhadap Keputusan Pembelian Produk Skincare dan Kosmetik Halal (Studi pada Generasi Z di DKI Jakarta) - Rifa Amalia; Dr. Sylvia Rozza, S.E., M.M. (Account : Jurnal Akuntansi, Keuangan dan Perbankan, 2022)
ABSTRACT The demand for halal products in the world is now increasing because the number of Muslim population continues to increase as well. But, the demand for halal cosmetics and beauty products is not that strong compared to the halal food sector. This research aims to analyze the effect of halal awareness, religiosity, lifestyle, and viral marketing on purchase decisions for halal skincare and cosmetic products. The population of this research is all Muslim consumers of Generation Z in DKI Jakarta who have bought and used any brand of skincare and cosmetics. The statistic tool used is SEM (Structural Equation Modeling with data processing LISREL 8.8. Number of samples taken is 235 respondents. Results showed that halal awareness, lifestyle, and viral marketing had a positive and significant effect on purchase decisions for halal skincare and cosmetics, while, religiosity did not affect. The results of this study are expected to be useful for industry stakeholder/producers of halal skincare and cosmetics in developing marketing strategies to reach consumer purchase decisions, especially Generation Z. Keywords: Halal Awareness, Religiosity, Lifestyle, Viral Marketing, Purchase Decisions